Does FX hedge mitigate the impact of exchange rate changes on credit risk? Evidence from a small open economy - Lorena Skufi; Adam Gersl (Charles University in Prague, Institute of Economic Studies (IES), 2025)
This study investigates the impact of exchange rate fluctuations on non-performing loans (NPLs), using a unique bank-by-bank dataset on lending to FX hedged and FX unhedged borrowers. Employing fixed effects and panel quantile regression, we analyze how changes in exchange rate affect the NPL ratio of hedged versus unhedged borrowers, differentiating between non-financial corporations and households and controlling for additional macroeconomic factors and bank-specific characteristics in Albania for the period from 2009 to 2023. Our empirical findings confirm that the sensitivity of unhedged non-financial corporations to exchange rate changes is higher than in the case of hedged borrowers. However, we find the opposite effect for households, where the risk seems to be for some reason higher for hedged borrowers.
Keywords: C23; C31; E5; G3; 330; Nonperforming loans; hedging; exchange rate; panel quantile regression; households and non-financial corporations